2022
DOI: 10.3390/ijerph19031034
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between Parents’ and Adolescents’ Sleep Duration

Abstract: This study explored the correspondence between adolescents’ sleep duration and that of their parents and identified the factors affecting the appropriate sleep duration for adolescents. The data of 795 adolescents from the Korea National Health and Nutrition Examination Survey (2015–2018) were analyzed. We used Cohen’s kappa coefficient to measure the correspondence between adolescents’ sleep duration and that of their parents. A multiple logistic regression analysis was used to identify the factors affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Less educated parents may have less time to raise their children. Moreover, longer screen times are associated with less leisure and exercise activities, and poorer sleep quality ( Jeon and Kim, 2022 ). Screen time is increasing in university students, especially before going to sleep; this can delay sleep and affect melatonin secretion, thus leading to a gradual decline in sleep ( Royant-Parola et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Less educated parents may have less time to raise their children. Moreover, longer screen times are associated with less leisure and exercise activities, and poorer sleep quality ( Jeon and Kim, 2022 ). Screen time is increasing in university students, especially before going to sleep; this can delay sleep and affect melatonin secretion, thus leading to a gradual decline in sleep ( Royant-Parola et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…When discussing adolescent sleep behavior, it is important to consider various key points such as the onset of sleep time, sleep patterns and duration and how they correlate with gender, the day of the week, parental sleep behaviors and other social factors. Studies have shown that the quality of sleep can be negatively affected depending on these factors [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Children's sleeping habits are directly influenced by those of their parents, and irregular or late sleeping habits in parents are associated with children's sleep disturbances, daytime sleepiness, and irregular eating habits (3). Furthermore, comparing mothers and fathers, the former's sleeping habits had a stronger impact on children's sleep than did the latter's in adolescents (3,4). A few studies have examined the association of preschool/elementary school children's sleeping habits and behavior with those of their parents.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the association of preschool/elementary school children's sleeping habits and behavior with those of their parents. Adolescents' sleep patterns are correlated with those of their parents, with factors such as the adolescents' sex, father's level of education, and parents' alcohol consumption frequency, particularly influencing the adolescents' sleep duration (4,5). These studies focused on sleep duration and quality but not on circadian rhythm-related factors such as chronotype.…”
Section: Introductionmentioning
confidence: 99%